2020
DOI: 10.3390/f11080896
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Analysis of Radial and Tangential Bending of Softwood and Hardwood at Static and Dynamic Loading

Abstract: This paper should primarily lead to a targeted expansion of the database dealing with bending characteristics, and thus help to understand the static and dynamic bending strength depending on the direction of external forces. Wood is very often used in the structural elements of buildings and wood products (e.g., furniture), in which there is both a static load, and in many cases a dynamic load, whilst the direction of loading is usually not considered. Specifically, the paper focuses on determining the bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
3
11
1
Order By: Relevance
“…However, in this research, it was found that the tangential pieces with a density of 0.39 g cm −3 resulted in higher moduli (≈11 GPa) than the radial specimens (≈9 GPa) of the same density. This mechanical response has also been found in coniferous and broadleaf species [83], in which the tangential pieces reached 17% higher than the specimens tested in the radial direction [84].…”
Section: Modulus Of Elasticity Of the Specimens Before Tensile Creepsupporting
confidence: 63%
“…However, in this research, it was found that the tangential pieces with a density of 0.39 g cm −3 resulted in higher moduli (≈11 GPa) than the radial specimens (≈9 GPa) of the same density. This mechanical response has also been found in coniferous and broadleaf species [83], in which the tangential pieces reached 17% higher than the specimens tested in the radial direction [84].…”
Section: Modulus Of Elasticity Of the Specimens Before Tensile Creepsupporting
confidence: 63%
“…It's known that ultrasonically determined mechanical values are generally higher than values those of statically determined. When compared to static results, an overestimation of MOE is the fact when using US, and differences were more pronounced in the wood species that has diffuse-porous structures (Borůvka et al 2020). As seen in Table 1, dynamic values were higher than static values for all treatment groups.…”
Section: Resultsmentioning
confidence: 88%
“…For instance, the values of dynamic and static bending strength of wood are different depending on the direction of the external force applied (in the radial or tangential loading direction). The difference of mean values in impact bending strength in the radial direction towards tangential was observed to be about 20% for beech [ 59 ]. Thermal conductivity of beech is about 18% higher in the radial than the tangential direction.…”
Section: Resultsmentioning
confidence: 99%